2016
DOI: 10.1007/s00134-016-4246-2
|View full text |Cite
|
Sign up to set email alerts
|

Rapid response teams improve outcomes: no

Abstract: Rapid response systems (RRS) have been widely endorsed and adopted by hospital systems in industrialized countries to respond to deteriorating patients outside the intensive care unit (ICU) [1]. There is face validity in the idea that a system that promotes early recognition of deterioration and the implementation of time-critical interventions would save lives. Recent systematic reviews point to the potential effectiveness of RRS, but important caveats need to be considered [2][3][4].The vast majority of stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Some proponents have questioned the existence of the tangible benefits of the RRS and suggested the need for higher level research and randomized controlled trials while others argued that the benefits are self-evident. Several authors have also attributed the conflicting evidence regarding the effectiveness of the RRS to delay or failure in ward clinicians to activate the RRT despite patients fulfilling the activation criteria [ 24 , 27 , 29 32 ]. An epidemiology review of adult RRT patients in Australia revealed that close to 50% of the activations were delayed [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some proponents have questioned the existence of the tangible benefits of the RRS and suggested the need for higher level research and randomized controlled trials while others argued that the benefits are self-evident. Several authors have also attributed the conflicting evidence regarding the effectiveness of the RRS to delay or failure in ward clinicians to activate the RRT despite patients fulfilling the activation criteria [ 24 , 27 , 29 32 ]. An epidemiology review of adult RRT patients in Australia revealed that close to 50% of the activations were delayed [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most common medical comorbidities were moderate to severe chronic kidney disease (defined as baseline estimated glomerular filtration rate <60 mL/min) affecting 239 (29.9%) patients, chronic pulmonary disease (219; 27.4%), ischaemic heart disease (202; 25.3%) and diabetes mellitus (193; 24.1%). The median Charlson comorbidity index (Table ) was six (IQR = 6), with 285 (35.6%) patients having a very high score (score >7), 166 (20.8%) a high score (score , ), 145 (18.1%) a medium score (score , ) and 204 (25.5%) a low score (0–3).…”
Section: Resultsmentioning
confidence: 99%
“…Such systems aim to rapidly identify clinically deteriorating patients (afferent limb) and activate appropriately trained teams (rapid response teams (RRT)) who provide resuscitative interventions (efferent limb), thereby preventing subsequent cardiac arrests and in‐hospital deaths . Whether RRS actually achieve these outcomes is still debated . Multiple studies, including several systematic reviews, report mixed results with regards to overall in‐hospital mortality …”
Section: Introductionmentioning
confidence: 99%
“…12,13,14,15 There is evidence of both improvement and lack thereof in patient outcomes in studies of RRTs. 16,17 Numerous factors may contribute to negative results, particularly in pediatrics, including the training and composition of RRTs and the diverse clinical conditions that pediatric RRTs must recognize and manage. In addition, the impact of a RRT may be attenuated at an institution where there is a strong preexisting patient care infrastructure.…”
mentioning
confidence: 99%